The Challenges of Lean Manufacturing Implementation in Kitting Assembly - A. F. H. , Fansuri; A. N. M., Rose; N. M. Zuki, N. M.; H., Ahmad (2017)
Literature studies shows that lean manufacturing goes way back with the original founder Eli Whitney in year 1799. The main purpose of lean manufacturing is to identify and eliminate waste in production. The application of lean manufacturing can be carried out in any industrial processes with regards to the understanding of lean principles, theories and practices. Kitting is one of the important aspects in a successful production. The continuous supply of materials from store to production has to be systematic and able to achieve lean standard for it to be successful. The objective of this paper is to review the implementation of lean manufacturing in kitting assembly. Previous papers show that, the implementation of lean manufacturing in kitting assembly may be beneficial to the organization such as reduce in space occupancy, part shortages, lead time and manpower. Based on previous research, some industries may tend to change between kitting and line stocking which are due to lack of understanding when implementing kitting and causes longer lead time and materials overflow in store. With a proper understanding on what to kit, where to kit, how to kit, why to kit and who kits the material with a standardised process flow may ensure the success of kitting.